Polarity Events in the Drosophila melanogaster Oocyte - Milas, Ana; Telley, Ivo A. (Frontiers in Cell and Developmental Biology, 2022)
Cell polarity is a pre-requirement for many fundamental processes in animal cells, such as asymmetric cell division, axon specification, morphogenesis and epithelial tissue formation. For all these different processes, polarization is established by the same set of proteins, called partitioning defective (PAR) proteins. During development in Drosophila melanogaster, decision making on the cellular and organism level is achieved with temporally controlled cell polarization events. The initial polarization of PAR proteins occurs as early as in the germline cyst, when one of the 16 cells becomes the oocyte. Another marked event occurs when the anterior–posterior axis of the future organism is defined by PAR redistribution in the oocyte, requiring external signaling from somatic cells. Here, we review the current literature on cell polarity events that constitute the oogenesis from the stem cell to the mature egg.